2013
DOI: 10.5194/isprsarchives-xl-2-w2-93-2013
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation on Different Number of Ground Control Points in Unmanned Aerial Vehicle Photogrammetric Block

Abstract: ABSTRACT:This paper presents a novel method of unmanned aerial vehicle image processing using photogrammetric technique. The study area consist different slope class which involves undulating area around the Skudai area, Malaysia. All photogrammetric methods were applied in this study including selection of test area, flight planning, camera calibration and image processing orientation. A new ground control point configurations is introduced in this study as a generic approach in unmanned aerial vehicle photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 9 publications
5
55
0
1
Order By: Relevance
“…Additionally, the abovementioned authors suggest the use of a higher number of GCPs [51,52]. Tahar [54] tested GCP configurations very similar to those presented in our study and acquired the best results using 8-9 GCPs.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, the abovementioned authors suggest the use of a higher number of GCPs [51,52]. Tahar [54] tested GCP configurations very similar to those presented in our study and acquired the best results using 8-9 GCPs.…”
Section: Discussionsupporting
confidence: 70%
“…They also showed that DSM accuracy is higher when the GCPs are installed in a way that they are visible on many images. The studies of Tahar et al [27], Tahar [28], as well as Rosnell and Honkavaara [29] also concluded that DSM accuracy increases with increasing number of GCPs. A similar conclusion was made in the study of Tonkin and Midgley [30], who additionally showed that when a certain number of GCPs is reached, the DSM accuracy does not increases further.…”
Section: Introductionmentioning
confidence: 99%
“…The importance and the number of GCPs necessary to ensure accuracy of UAS image construction have been previously discussed by other researchers. [46][47][48] In terms of geometric quality, the accumulated horizontal and vertical error was 0.7 cm∕pixel in orthomosaic and CSM from 2-weeks prior to flowering, and 0.5 cm∕pixel for the flowering raster products. Furthermore, a woody table (dimensions ¼ 0.8 m length × 0.4 m wide × 0.6 m height) was used for nonvegetation geometric evaluation.…”
Section: Crop Surface Model and Orthomosaic Generationmentioning
confidence: 99%